Object-oriented design metrics as early quality indicators of faultyclasses and components - Lee, S.P.; Loh, C.H. (2009)
The primary objective of object-oriented design metrics is to evaluateobject-oriented design quality characteristics such as traceability, complexity,testability, and maintainability in a quantitative way through establishingrelationships between object-oriented design quality characteristics, andobject-oriented design metrics such as depth of inheritance tree, the number ofchildren, and response for a class. In this paper, we propose a set of improvedobject-oriented design metrics to measure the design quality of object-orientedsystems at the inheritance level specializing on incremental and subtyp-inginheritance. The metrics serve as early quality indicators of object-orienteddesign faults such as faulty classes and components in object-oriented systems.We augmented the metrics from two existing metrics, namely Attribute InheritanceFactor and Method Inheritance Factor. The metrics specialize on measuring theoverall inheritance density of classes and components based on several qualityattributes such as maintainability and testability. The metrics are expressed asindexes, ranging from 0 (i.e. indicating favourable) to 1 (i.e. indicating notfavourable). ICIC International Â© 2009.